تأثير استراتيجية إدارة الموارد البشرية على وظيفة تكوين الرأس المال البشري في منظومة الإدارة العامة في لبنان - عطار, وائل (جامعة الوادي - University of Eloued, 2021)
إنّ عمليّة تبنّي تطبيق المفاهيم الإدارية الحديثة ومن أهمّها استراتيجيّة الموارد البشريّة تعدّ من المتطلّبات الهامّة لمواكبة التّطوّرات والتّحدّيات المستمرّة الّتي تواجه المنظّمات، لذا فإنّه يجب على القيادات الإداريّة في الأجهزة الحكوميّة أن تتولّى اهتماماً خاصّاً لتطبيق هذه المفاهيم وترجمتها على أرض الواقع بما يضمن توفير المستلزمات الأساسيّة والمتطلّبات الخاصّة بنجاحها. هدفت هذه الدّراسة لتشخيص واقع تكوين الرأس المال البشري في منظومة الإدارة العامّة، وإلى وضع استراتيجيّة متكاملة لتكوين الموارد البشريّة تتضمّن آليّات محدّدة وواضحة لجعلها قابلة للحياة. كذلك لتقديم اقنراحات وتوصيات للمعنيّين في منظومة الإدارة العامّة اللبّنانيّة تسهم في تطوير وتحسين واقع إدارة الموارد البشريّة. ومن خلال مراجعة الأبحاث العلميّة في هذا المجال، تمّ صياغة نموذج الدّراسة وفرضيّتها وتصميم إستبانة لجمع البيانات. وقد تألفت عيّنة الدّراسة من الموظّفين في الوزارات اللّبنانيّة والإدارات العامّة، وقد تمّ استخدام برنامج التحليل الإحصائي (SPSS) لتحليل البيانات. وقد كشفت عمليّة تحليل البيانات نتائج متعددة أهمها: وجود علاقة طرديّة بين الواقع الإستراتيجي لإدارة الموارد البشريّة وبين واقع وظيفة تكون الرأس الرمال البشري في منظومة الإدارة العامّة اللّبنانيّة. وختاماً خلصت الدّراسة إلى مجموعة توصيات أبرزها: • اقتناع وتوجيه الدّولة اللّبنانيّة على تنمية الموارد البشريّة كرأس مال فكري يجب أن تُحسن تكوينه باعتباره المصدر الأساس لامتلاك القدرة التّنافسيّة لمواجهة تحدّيات المستقبل ولما له من دور أساسي كشريك استراتيجي في التّنمية الإداريّة وبالتّالي في تحسين مستوى الخدمات الحكوميّة للمواطن. • وضع رؤية واضحة يمثّل فيها الموظّف رأسمال بشري أساسي في بناء الميزة التّنافسيّة، واعتباره شريك في إعداد وتنفيذ الإستراتيجيّات. The process of adopting the application of modern management concepts, the most important of which is the human resources strategy, is one of the important requirements to keep abreast with the ongoing developments and challenges faced by organizations. Therefore, the administrative leaders in the governmental bodies must take full responsibility for the application of these concepts and translate them on the ground in order to ensure the provision of basic supplies and special requirements for their success. This study aimed to diagnose the reality of recruiting in the public administration system to develop an integrated strategy for human resources that includes specific and clear mechanisms to make it viable. As well as to provide suggestions and recommendations to stakeholders in the Lebanese public administration system those contribute to the development and improvement of the reality of human resources management. Through the review of scientific research in this area, the study model and hypotheses were formulated and a questionnaire was designed to collect data. The study sample consisted of employees in the Lebanese ministries and public administrations. The statistical analysis program (SPSS) was used to analyze the data. Analysis of the data revealed several results, the most important of which: - The existence of a relationship between the strategic reality of the management of human resources in the Lebanese public administration system and the reality of the function of recruiting in the Lebanese public administration system. Finally, the study concluded with a set of recommendations: - Conviction of the Lebanese state and its guidance on the development of human resources as an intellectual capital should improve its composition, development and protection as the main source of competitiveness to meet the challenges of the future and its role as a strategic partner in administrative development and thus in improving the level of government services for citizens. - Establish a clear vision in which the employee represents an essential human capital in building competitive advantage and as a partner in the preparation and implementation of strategies.
Impact of human resources management strategy on the function of human capital formation in the public administration system in Lebanon
مقال
Keywords: الإدارة الاستراتيجية للموارد البشرية ; ﺇﺩﺍﺭﺓ ﺍﻟﻤﻭﺍﺭﺩ ﺍﻟﺒﺸﺭﻴﺔ ; الإدارة العامة ; ﺍﻻﺨﺘﻴﺎﺭ والتعيين ; تكوين الرأس المال البشري